Investigation of the transport properties of microcrystalline silicon by time-of-flight (TOF) - Serin, M; Harder, N; Carius, R (SPRINGER, 2003)
The transport properties of microcrystalline silicon have been studied by the time-of-flight technique on a 6.3-mum thick n-i-p solar cell illuminated from the p-side (n-side) to obtain electron (hole) current transients. The transients exhibit dispersive behavior. At room temperature, drift-mobility values of about 2-4 cm(2) V(-1) s(-1) and 2 cm(2) V(-1) s(-1) were deduced for electrons and holes, respectively. The dispersion parameters alpha(l) and alpha(2), as determined from the pre- and post-transit slopes of the current transients were similar to those for a-Si:H. (C) 2003 Kluwer Academic Publishers.
Keywords: SI-H; Engineering; Materials Science; Physics